Continuous removal of caffeine in a horizontal-flow anaerobic immobilized biomass bioreactor: identification of transformation products - Martins, Giovana Silva [UNESP]; Rodrigues, Thaís [UNESP]; Lamarca, Rafaela Silva [UNESP]; Ayala-Durán, Saidy Cristina [UNESP]; da Silva, Bianca Ferreira; de Lima Gomes, Paulo Clairmont Feitosa [UNESP] (Springer Nature, 2023)
Anaerobic bioreactors are an efficient technology for the biodegradation of emerging contaminants in environmental matrices. In this work, a horizontal-flow anaerobic immobilized biomass (HAIB) bioreactor was used to remove caffeine (CAF), which is frequently found in various aqueous matrices. The acrylic bench top bioreactor, with dimensions of 100 × 5.00 cm, was operated with a hydraulic retention time (HRT) of 12 h, during 45 weeks, under mesophilic conditions. The operation was performed in 4 phases: without CAF addition (phase I); CAF spiked at 300 μg L−1 (phase II); CAF at 600 μg L−1 (phase III); and CAF at 900 μg L−1 (phase IV). Samples of bioreactor influent and effluent were analyzed by liquid chromatography/tandem mass spectrometry (LC–MS/MS). The bioreactor removed organic matter (OM) and CAF with efficiencies of 88 and 93%, respectively. The first-order apparent removal constant (Kapp) values for OM and CAF were 0.419 and 0.304 h−1, respectively. Five transformation products (TPs) were identified, with m/z 243, 227, 211, and 181 (two products). The HAIB bioreactor is a suitable system for the removal of CAF present in wastewater, even at a concentration level of µg L−1.
Keywords: Caffeine; Horizontal-flow anaerobic immobilized biomass bioreactor; Transformation products